Computational characterization of the secondary droplets formed during the impingement of a train of ethanol drops. (February 2020) - Markt, David; Pathak, Ashish; Raessi, Mehdi; Lee, Seong-Young; Torelli, Roberto
This article uniquely characterizes the secondary droplets formed during the impingement of a train of ethanol drops, using three-dimensional direct numerical simulations performed under conditions studied experimentally by Yarin and Weiss. Our numerical results have been previously validated against experimental data demonstrating the ability to accurately capture the splashing dynamics. In this work, the predictive ability of the model is leveraged to gain further insight into secondary droplet formation. We present a robust post-processing algorithm, which scrutinizes the liquid volume fraction field in the volume-of-fluid method and quantifies the number, volume and velocity of secondary droplets. The high-resolution computational simulations enable secondary droplet characterization within close proximity of the impingement point at small length and time scales, which is extremely challenging to achieve experimentally. By studying the temporal evolution of secondary droplet formation, direct connections are made between liquid structures seen in the simulation and the instantaneous distribution of secondary droplets, leading to detailed insight into the instability-driven breakup process of lamellae. Time-averaged secondary droplet characteristics are also studied to describe the global distribution of secondary droplets. Such analysis is vital to understanding fuel drop impingement in direct injection engines, facilitating the development of highly accurate spray–wall interaction models for use in Lagrangian solvers.